2018
DOI: 10.1371/journal.pone.0195724
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between endothelial damage and repair capacity in chronic obstructive pulmonary disease

Abstract: BackgroundCirculating endothelial microparticles (EMPs) and progenitor cells (PCs) are biological markers of endothelial function and endogenous repair capacity. The study was aimed to investigate whether COPD patients have an imbalance between EMPs to PCs compared to controls and to evaluate the effect of cigarette smoke on these circulating markers.MethodsCirculating EMPs and PCs were determined by flow cytometry in 27 nonsmokers, 20 smokers and 61 COPD patients with moderate to severe airflow obstruction. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 46 publications
(66 reference statements)
2
41
0
1
Order By: Relevance
“…Results of the present study indicate that pulmonary and systemic vascular impairments are interrelated in COPD. These findings concur with the previous observations of altered markers of vascular competence (defined as an imbalance between injury and repair capacity of the endothelium) in COPD patients with PVD, 5 suggesting common pathways in the pathobiology of alterations in both vascular territories.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results of the present study indicate that pulmonary and systemic vascular impairments are interrelated in COPD. These findings concur with the previous observations of altered markers of vascular competence (defined as an imbalance between injury and repair capacity of the endothelium) in COPD patients with PVD, 5 suggesting common pathways in the pathobiology of alterations in both vascular territories.…”
Section: Discussionsupporting
confidence: 92%
“… 1 Indeed, cardiovascular disease is a major cause of death in COPD patients, accounting for 25% of the overall mortality. 2 Previous studies have shown that COPD is associated with changes in systemic vascular function 3 , 4 and circulating biomarkers of vascular competence 5 thereby suggesting the presence of associated peripheral artery disease. 6 The severity of endothelial dysfunction in systemic arteries, as assessed by flow-mediated dilation (FMD), 7 correlates with the severity of airflow obstruction and the extent of emphysema in COPD.…”
Section: Introductionmentioning
confidence: 99%
“…For the request "endothelium + COPD," it offers 335 publications, of which 72 after 2015, and for the request "endothelium + smoking," it offers 1859 publications, of which 188 after 2015. This indicates the relevance of this area of research and demonstrates the hopes of researchers finding new opportunities for therapeutic and prophylactic effects on this relationship in the pathogenesis of tobacco-related lesions, COPD, and emphysema [17][18][19][20][21][22][23].…”
Section: Endothelium-related and Neuro-mediated Mechanisms Of Emphysementioning
confidence: 69%
“…It has been shown that COPD patients present endothelial dysfunction in both pulmonary and systemic arteries at early disease stages [79]. This endothelial damage may result from an imbalance between vascular injury and the body’s repair capacity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced number and function of circulating PCs has been established as an independent prognostic factor associated with endothelial dysfunction, high cardiovascular risk and increased mortality [1416]. In COPD, few studies to date have investigated the number of circulating PCs [10, 12, 17]. We and others have previously shown reduced levels of circulating PCs in COPD patients, as compared to controls [10, 12, 17].…”
Section: Introductionmentioning
confidence: 99%